EVALUATING FINANCIAL SYNERGY IN BANK MERGER: RANKING MERGER OPTIONS AND ANALYZING INFLUENTIAL FACTORS - Roy, Gourav (Asian Finance & Banking Review, 2024)
Given the excess number of banks, the Central Bank of Bangladesh recently saw mergers as a good solution for economic development in an emerging economy like Bangladesh. Still, the question remained: which bank should merge with whom to create value, known as financial synergy? The study investigates which mergers add value to financial synergy and which do not. Additionally, the study scrutinizes the financial factors that influence the financial synergies resulting from the mergers of the participating banks. This study employs fifty-five possible cases of mergers found in eleven banks, including government, non-government, and specialized banks, to conduct financial synergy valuations on the average of five years of financial information. The methodology employs simulation, sensitivity, trend, scenario, Ordinary Least Squares (OLS), and Mixed Effect Generalized Linear Model (MEGLM) to solve the research questions. The results reveal that mergers between BKB and RAKUB, EXIM and Padma, NBL, and UCB can result in positive financial synergy among the six cases proposed by the central bank. The results also show that financial factors including debt to capital, reinvestment rate, return on capital, cost of debt, and revenues significantly impact the financial synergy. The findings of the study suggest the central bank merge based on the ranking provided in the study, considering the influential factors in mergers among banks. These findings contribute to the existing field of study by optimizing the synergy valuation strategies for bank mergers in a complex environment of bank types. JEL Classification Codes: G34, G32, C51, G21.